2013
DOI: 10.1016/j.jpeds.2013.05.040
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Adropin Concentrations in Pediatric Obstructive Sleep Apnea: Potential Relevance to Endothelial Function

Abstract: Objective To test the hypothesis that levels of adropin, a recently discovered peptide that displays important metabolic and cardiovascular functions, are lower in obstructive sleep apnea (OSA), especially when associated with endothelial dysfunction. Study design Age-, sex- and ethnicity-matched children (mean age: 7.2±1.4 years) were included into one of three groups based on the presence of OSA in an overnight sleep study, and on the time to post-occlusive maximal reperfusion (Tmax>45 sec) with a modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 30 publications
1
42
1
Order By: Relevance
“…Because adropin had been proposed as a hepatocyte-secreted protein (1), it was expected that adropin could be found in the liver and blood samples. The controversial findings regarding circulating adropin (6,8,9,13) led us to reinvestigate the biochemical properties of adropin.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because adropin had been proposed as a hepatocyte-secreted protein (1), it was expected that adropin could be found in the liver and blood samples. The controversial findings regarding circulating adropin (6,8,9,13) led us to reinvestigate the biochemical properties of adropin.…”
Section: Resultsmentioning
confidence: 99%
“…Correlations between circulating adropin levels and different pathophysiological states in mice and humans have been reported (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). In brief, the circulating concentration of adropin was reduced markedly in several metabolic diseases, including obesity-associated insulin resistance (1,5,11); obesity-related, nonalcoholic fatty liver disease (11); gestational diabetes mellitus (7); and endothelial dysfunction (6,8,14). However, conversely, other studies found that plasma adropin levels in humans were not correlated inversely with obesity on the basis of body mass index (6,8,13) or with endothelial dysfunction (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the linkage between circulating adropin levels and other various pathophysiological conditions in mammals have been reported, the exact link with adropin remains elusive. Some studies showed that plasma adropin levels were linked with several metabolic diseases, including insulin resistance ) and nonalcoholic fatty liver disease (Sayin et al 2014) and endothelial dysfunction (Gozal et al 2013), whereas other studies found that plasma adropin levels were not correlated with endothelial dysfunction in humans with heart failure (Lian et al 2011) or with BMI in patients with type 2 diabetes mellitus (Topuz et al 2013). Besides, adropin may be involved in the metabolic adaptation to fasting, although these data are still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…20 Over the last decade, a constellation of morbidity-related biomarkers has been proposed for pediatric OSAS, and a scoping review was previously published and investigated potential associations and predictive abilities of such published candidate biomarkers in OSAS-induced morbidities in both adults and children. 21 In this article, we focus on the more promising of such biomarkers, and particularly on those potentially contributing to detection and monitoring of cardiometabolic morbidity (see Table 1 [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] residual OSAS following T&A. 23 On the basis of the interindividual variability of the responses to T&A we previously found in a large panel of inflammatory markers among a large group of obese children with OSAS, 24 it is likely that use of CRP alone, rather than as a component of a multiarray panel, may not provide sufficiently accurate prediction of CVD risk or its resolution with treatment.…”
mentioning
confidence: 99%